Clinical and paraclinical characteristics in pediatric patients with acute recurrent and chronic pancreatitis: a cohort in Mexico - José A. Argüello-López; Eustorgio S. García-Cárdenas; América L. Miranda-Lora; Gerardo Blanco-Rodriguez (Permanyer, 2023)
Background: Acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) are infrequent clinical entities in pediatric patients, as less than 8% of the literature mentions this population. This study aimed to describe the clinical and paraclinical profile, and the etiology related to patients with ARP and CP attended at a tertiary-level healthcare institute in Mexico. Methods: We conducted a retrospective study from medical records of patients with ARP and CP attended between 2010 and 2020, analyzing the clinical characteristics, imaging studies, and the etiology associated with each patient. Results: We analyzed 25 patients: 17 were diagnosed with ARP, and eight with CP. The main etiology identified was an anatomical alteration of the pancreatic duct (32%); pancreas divisum was the most prevalent condition. In 48% of the population, the etiology was not identified. The group with CP was higher in frequency for calcifications and dilation of the pancreatic duct (p < 0.005) compared to the ARP group. Conclusions: The main etiology for ARP and CP was an anatomical alteration of the pancreatic duct; however, in almost half of the cases, no established cause was identified. Although comparing our results with those offered by large cohorts such as the INSPPIRE group can be complex, we found relevant similarities. Currently, the data obtained from this first descriptive study are the foundation for future research in the field of Mexican pediatric pancreatology.